Cell-based and cell-free immunotherapies for glioblastoma: current status and future directions - Wang, Mingming; Wang, Xiaojie; Jin, Xiaoyan; Zhou, Jingjing; Zhang, Yufu; Yang, Yiyuan; Liu, Yusi; Zhang, Jing (Frontiers in Immunology, 2023)
Glioblastoma (GBM) is among the most fatal and recurring malignant solid tumours. It arises from the GBM stem cell population. Conventional neurosurgical resection, temozolomide (TMZ)-dependent chemotherapy and radiotherapy have rendered the prognosis of patients unsatisfactory. Radiotherapy and chemotherapy can frequently induce non-specific damage to healthy brain and other tissues, which can be extremely hazardous. There is therefore a pressing need for a more effective treatment strategy for GBM to complement or replace existing treatment options. Cell-based and cell-free immunotherapies are currently being investigated to develop new treatment modalities against cancer. These treatments have the potential to be both selective and successful in minimizing off-target collateral harm in the normal brain. In this review, several aspects of cell-based and cell-free immunotherapies related to GBM will be discussed.